THE EFFECT OF COMMUNITY-BASED DISASTER PREPAREDNESS TRAINING ON KNOWLEDGE AND ATTITUDE CADRES IN TSUNAMI-PRONE AREAS OF PADANG CITY - Kintan Resqitha Ekaputri; Elsi Dwi Hapsari; Syahirul Alim (Jurnal Ilmu-Ilmu Kesehatan, 2026)
The high threat of tsunami disaster risk and the low knowledge capacity and attitude of cadres mean that it is necessary to provide training to increase the knowledge and attitude of cadres in responding to tsunami disasters. However, there is no effective community-based disaster preparedness training available for cadres to improve knowledge and attitudes. This study aims to determine the effect of community-based disaster preparedness training on the knowledge and attitudes of tsunami cadres in tsunami-prone areas of Padang City. The type of research is pre-experimental using a one group pretest-posttest research design using a double posttest. Respondents were cadres in Ulak Karang Utara Subdistrict, Padang City, totaling 20 respondents using total sampling. The intervention carried out was providing community-based disaster preparedness training to cadres for one day. The knowledge and attitude instruments were created by researchers and have been tested for validity and reliability. Data analysis used the repeated ANOVA test. There was an increase in the average value of knowledge pre-test and post-test 1 (8,05 ± 1,905 vs 10,00 ± 1,257), and there was a decrease in the average value of post-test 1 and post-test 2 (10,00 ± 1,257 vs 9,65±1,531). There was an increase in the average attitude value of pre-test and post-test 1 (51,35 ± 4,603 vs 54,05 ±4,359), as well as post-test 1 and post-test 2 (54,05 ± 4,359 vs 54,95 ± 2,781). There was an effect of disaster preparedness training on knowledge (p<0,001) and attitudes of cadres (p = 0,003). Providing community-based disaster preparedness training has a significant influence on the knowledge and attitudes of cadres.